PENYELENGGARAAN DAN PENGELOLAAN BUS RAPID TRANSIT TRANS TANGERANG BERDASARKAN UNDANG-UNDANG NOMOR 8 TAHUN 1999 DAN UNDANG-UNDANG NOMOR 22 TAHUN 2009 TENTANG LALU LINTAS DAN ANGKUTAN JALAN - nana indriati (iLearning Journal Center, 2019)
ABSTRACT This study aims to identify and explain the fulfillment of labor rights under Law No. 13 of 2003 on employment, enforcement of employment law against employers / employers not fulfilling the protection of workers' rights, the effectiveness of the role of trade unions in the framework of fighting for the fulfillment of labor rights in the Regency Tangerang and the factors hindering the effectiveness of the role of trade unions in the framework of fighting for the fulfillment of labor rights in the Tangerang Regency region and the efforts made in overcoming these obstacles. The research method used is qualitative method. Used to answer the formulation of the proposed problem and the purpose of the research. Key informants used are from representatives of trade unions in Tangerang District and review documents from various government agency reports. The result of the research explains that the role of All-Indonesia Workers Union (SPSI) of Tangerang Regency in making and implementing Collective Work Agreement has been effective.